New Ideas and Critical review of Middle Eocene Gercus Formation, Kurdistan Region, NE-Iraq - Karim, Kamal Haji; Khanaq, Polla A; Baziany, Mushir M. (Sulaimani Journal for Pure and Applied Sciences, 2018)
In Iraq, Gercus Formation (Middle Eocene) crops out now near boundary between Low and High Folded Zone and generally consisted of red claystone and sandstone with occasional beds of conglomerate. Lithologically, it changes toward the southwest to carbonatesiliclastics of either Khurmala or Aliji Formations inside the Low Folded Zone. All previous studies have concluded that the environment of the formation was fluvial and deltaic of continental mollasse facies with possible some shallow marine sediments at its lower part. Conversely, the most recent two studies have assigned two different, opposite environments of the formation, which are deep marine (turbidite facies), and desert environments. The aim of the present study is critical and objective analysis of the previous studies in addition to introduction of new ideas that are opposite to deep marine and aeolian environments. The study gives many evidences and features for justification of the introduced new ideas, which are revealing the actual environment of the formation. This reveal is depended on the field and regional correlation in areas of boundary between High and Low Folded Zone (area of exposure of Gercus Formation) and area of Imbricated and Thrust Zone where its equivalent in age and facies (unit five of Red Bed Series) is exposed. The present study supports neither the deep marine turbidite nor the desert erg system of the previous studies. The present study proves that the Gercus Formation consists of the distal alluvial fan and its proximal part is unit five of Red Bed.
Keywords: Gercus Formation; turbidite sediment; Red Bed Series; Aeolian sediments; continental sediments